COASTAL RESTORATION THROUGH COMMUNITY PARTICIPATION: In Meuraxa District, Banda Aceh - Faiza Aidina (Rumoh, 2018)
Tsunami in 2004 has changed urban condition in Banda Aceh especially along north west coast area.This Strecth line area has lost its vitality as an attractive urban area, in Banda Aceh those situation happened in Meuraxa district Banda Aceh (2005-2006). This qualitative research attempt to seek a way to restore this area to former condition. The idea is the conversion of waste land into more productive land. The action plan is consisted in two phase : 1.to create mangrove cultivation community and sylvofishery, 2. To create a community hub for trading, cultural activity, and recreational place. The analysis start from major scale and then focus on selected location as a starting point for a proposed action plan.